Whether the intraoperative irradiation influences the life quality of lung cancer patients? - B. S. Khodkevich; A. A. Zaviyalov; S. V. Miller (Бюллетень сибирской медицины, 2006)
The life quality of patients with lung cancer after the intraoperative irradiation with a dose 15 Gy during the surgery (loband pneumonoectomies) for the period of two years has been studied. The form developed by the European Organization for Research and Treatment of Cancer EORTC QLQ-C 30 and the QLQ-LC 13 module were used. It is shown that the life quality of patients with lung cancer after combined therapy is determined mainly by the volume of surgery made, rather than by the adjuvant therapy conducted. Of great importance for patients was the period needed for the adaptation of the organism to new living conditions. In general, no significant differences in the main life quality indices were revealed among patients of both groups. Based on the results obtained, one can say that the addition of surgery with intraoperative radiotherapy with a total focal dose 15 Gy does not lead to the considerable worsening of life quality of patients and can be recommended for clinical application.